PERANAN LEMBAGA PUNYIMBANG ADAT LAMPUNG SAIBATIN DALAM MELESTARIKAN TRADISI BUBALAH - Netika Wuri; Hermi Yanzi; Yunisca Nurmalisa (Jurnal Kultur Demokrasi, 2016)
This research was done in order to describe the roles of Punyimbang Adat Lampung Saibatin as an institution in sustaining Bubalah tradition. The method that was used in this research was a qualitative method. The subjects of the research was Punyimbang Adat (respected figures in the village), the chief of the village and the community in Kedaloman. The data were obtained by using interviews, observation and documentation. Extra time and triangulation were used in this research in order to made the data more valid and credible. The result of this research showed that there is a significant roles from the Institute of Punyimbang Adat Lampung Saibatin in sustaining the tradition of Bubalah by accommodating and distributing the aspirations or public opinion in resolving problems that occurin the community. And also, preserving, developing and empowering the culture Lampung. In addition, creating relationships that democratic and harmonious between Punyimbang Adat and the society is one of the important role.Tujuan penelitian ini adalah mendeskripsikan peranan Lembaga Punyimbang Adat Lampung Saibatin dalam melestarikan tradisi Bubalah. Metode penelitian yang digunakan dalam penelitian ini adalah metode kualitatif. Subjek dalam Penelitian ini adalah Punyimbang Adat, Kepala Desa dan Tokoh Masyarakat di Desa Kedaloman. Teknik pengumpulan data yang digunakan adalah wawancara, observasi dan dokumentasi. Uji kredibilitas data menggunakan perpanjangan waktu dan triangulasi. Hasil penelitian ini adalah terdapat peranan Lembaga Punyimbang Adat Lampung Saibatin dalam melestarikan tradisi Bubalah dengan menampung dan menyalurkan aspirasi atau pendapat masyarakat dalam menyelesaikan masalah yang timbul dalam masyarakat, melestarikan, mengembangkan dan memberdayakan kebudayaan Lampung, dan menciptakan hubungan yang demokratis dan harmonis antara punyimbang adat dengan masyarakat.Kata kunci: lembaga punyimbang adat, pelestarian, tradisi bubalah.